Replacement artemia nauplii by Tubifex sp. In reaving Walking Fish Larvae (Anabas testudineus) - Erma Juniarti; Sukendi Sukendi; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abtract This research was conducted in December until January 2018 in the  Fish Breeding and hatcheryDepartment of Aquaculture, Marine Fisheries Faculty University of Riau, Pekanbaru. The purpose of this research is to know how the replacement of Artemia nauplii with worm Tubifex sp. on the rearing of fish larvae (Anabas testudineus). The treatments  applied in this study were the P1: feeding Artemia nauplii(40 days) P2: feeding Artemia nauplii (10 days) and feeding Tubifex sp. (30 days) P3: feeding Artemia nauplii after (20 days) and feeding Tubifex sp. (20 days) P4: feeding Artemia nauplii (30 days) and feeding Tubifex sp. (10 days), P5: feeding Tubifex sp. (40 days). The results showed that the worm Tubifex sp. Artemia nauplii can be replaced as feed early or up to 20 days. Maintenance on the larvae of fishes anabas were 1.17 grams of absolute weight growth, 5.81 cm of absolute length growth, specific growth rate was 11.92% and Survival Rate was 83.33%. Water quality during the study i.e. the temperature range was 26-290C, pH range was between 6-7 and DO was 4.2-5.2. Keywords : Replacement, Artemia nauplii, Tubifex sp. Walking Fish Larvae (Anabas testudineus)